How India’s food-based safety net is responding to the COVID-19 lockdown - Roy, Devesh; Boss, Ruchira; Pradhan, Mamata (International Food Policy Research Institute, 2020)
The food relief program can also be used as a medium to communicate key messages about the epidemic, including on social distancing and other public health and safety measures. COVID-19 may be with us for a year or more; India’s relief package is only the beginning. Going forward, the government needs a contingency plan focusing on how much, and for what length of time, the food system can continue to supply the social safety net in its current configuration. The lives and livelihoods of hundreds of millions depend on it.